Contaminated bone grafts and tuberculosis in three spine surgery patients: a case series - Naveed, Mustafa; Ruan, Tiffany; Sharma, Vishakha; Vien, Hon (International Journal of Research in Orthopaedics, 2023)
Tuberculosis (TB) is a global health issue affecting millions of people every year. Previous articles displayed cases of TB resulting from contaminated bone grafts used in spinal surgeries. However, deeper understanding about the serious health consequences for patients affected by TB-infected bone grafts is lacking. Here, we discuss three unique patients who contracted TB after undergoing lumbar spinal surgery. We describe three patient cases in which individuals initially presented with back pain, underwent required lumbar spinal fusion surgery with bone graft implants, and, afterwards, contracted TB. All patients were given RIPE therapy, had additional surgery to remove the faulty hardware, and lived with significant and prolonged pain. In addition, patient X experienced night sweats, patient Y had a subcutaneous abscess positive for TB, and patient Z had severe burning pain, rash, and sweats. Altogether, we emphasize the importance of increasing our awareness about the potential risks and complications associated with utilizing contaminated surgical products. We encourage healthcare professionals to take necessary precautions to ensure the safety of their patients by screening bone grafts for potential pathogens and practicing proper sterilization techniques.